2020
DOI: 10.1021/acs.jpcc.0c07334
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Optical Characteristics of Diketopyrrolopyrrole Molecules in the Solid State by Alkyl Side Chains

Abstract: The optical properties of two sets of donor–acceptor–donor molecules with terminal bithiophene donor units and a central diketopyrrolopyrrole (DPP) acceptor unit are studied. The two sets differ in the alkyl chains on the DPP, which are either branched at the α-carbon (3-pentyl) ( 1 – 4 ) or linear ( n -hexyl) ( 5 – 8 ). Within each set, the molecules differ by the absence or presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 67 publications
1
35
0
Order By: Relevance
“…49 UV-vis obtained for DPP-4T showed that changing the side chains from linear to branched had subtle effects on the spectra in solution, while in thin films the linear side chains showed stronger intermolecular interactions. 50 The effects of different end groups was investigated for different end groups such as hydrogen atoms, thiophene rings or pyrene segments. [51][52][53] Finally, optical spectra have shown evidence of Hand J-aggregates 54 in polymers of the DPP family.…”
Section: Introductionmentioning
confidence: 99%
“…49 UV-vis obtained for DPP-4T showed that changing the side chains from linear to branched had subtle effects on the spectra in solution, while in thin films the linear side chains showed stronger intermolecular interactions. 50 The effects of different end groups was investigated for different end groups such as hydrogen atoms, thiophene rings or pyrene segments. [51][52][53] Finally, optical spectra have shown evidence of Hand J-aggregates 54 in polymers of the DPP family.…”
Section: Introductionmentioning
confidence: 99%
“…This result agrees with that reported in the literature, which points out the small effect of the side alkyl chains on the photophysics of DPPs derivatives in solution (although this effect becomes significant in the solid-state). 43 Thus, to decrease the computational cost and turn the subsequent DFT/MRCI calculations feasible, the alkyl chains were substituted by methyl groups (Figure 1a and c).…”
Section: Photophysics Of the Monomer And Dimermentioning
confidence: 99%
“…17 The N-alkyl groups on DPP derivatives play a crucial role not only in the improvement of the solubility but, depending on their nature, they can also affect the structural, conformational, and solid-state organization through intra-and intermolecular interactions with strong consequences on the electronic and photophysical properties. [18][19][20][21][22] For instance, the - stacking interactions (which often determine a quenching of the photoluminescence in the solid state for DPP-based fluorophores) can be considerably reduced by using sterically demanding side chains such as benzyl groups [23][24][25] or -branched alkyl groups. 19,26 This latter class of N-alkyl substituents should be regarded as a practical expedient for introducing stereogenic centres close to the DPP core, opening the way towards a cutting-edge class of chiral fluorophores with enhanced chiroptical properties.…”
Section: Dpp Alkylationmentioning
confidence: 99%